2019
DOI: 10.1109/access.2019.2943351
|View full text |Cite
|
Sign up to set email alerts
|

Detecting At-Risk Students With Early Interventions Using Machine Learning Techniques

Abstract: Massive Open Online Courses (MOOCs) have shown rapid development in recent years, allowing learners to access high-quality digital material. Because of facilitated learning and the flexibility of the teaching environment, the number of participants is rapidly growing. However, extensive research reports that the high attrition rate and low completion rate are major concerns. In this paper, the early identification of students who are at risk of withdrew and failure is provided. Therefore, two models are constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…GLM is a statistical method that comes under supervised machine learning algorithms which assumes every number of observations has a distribution like polynomial, binomial, gamma, average (Al-Shabandar et al 2019). GLM gives a continuous output of dependent variables by evaluating independent variables and performs linearly.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…GLM is a statistical method that comes under supervised machine learning algorithms which assumes every number of observations has a distribution like polynomial, binomial, gamma, average (Al-Shabandar et al 2019). GLM gives a continuous output of dependent variables by evaluating independent variables and performs linearly.…”
Section: Methodsmentioning
confidence: 99%
“…(Geigle and Zhai 2017), Two-layer hidden Markov Model was used for predicting accuracy percentage of At-risk students on the basis of student's behavioural patterns and results demonstrated that Low motivational status, withdrawal of course at early stage and failure rate are the major concerns and got an accuracy of 80.93%. (Al-Shabandar et al 2019), At-risk students accuracy was predicted using machine learning algorithms which includes GLM, Gradient Boost machine algorithm, Random Forest. The results of their work demonstrated an accuracy of 91%, 90%, 91% respectively.…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…However, potentially low achieving students are more di cult to detect in an online course, since the lecturers and students are not within the same room and the time for online face to face contact is limited and often shorter than in-class meetings. Therefore, early detection of low achieving students will provide more opportunity to overcome some of their challenges and problems in achievement [6,7].…”
Section: Introductionmentioning
confidence: 99%